THE RELATIONSHIP BETWEEN WORK FATIGUE AND JOB SATISFACTION WITH THE WORK PRODUCTIVITY OF NURSES IN EFARINA HOSPITAL INPATIENT WARDS, 2016 - Nurmala (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2022)
Fatigue is a problem that needs attention. All types of work, both formal and informal, cause work fatigue. Work fatigue will reduce performance and increase work errors. Decreasing performance means decreasing work productivity. Job satisfaction is also an important target in human resource management because it directly or indirectly affects the work productivity of employees in an organization or company. analytic with a cross-sectional design to analyze the relationship between work fatigue and type of research. Tengku Mansyur Tanjungbalai Measurement of work fatigue, job satisfaction and work productivity respectively using a questionnaire. Work fatigue uses KAUPK2, job satisfaction uses a job satisfaction questionnaire while measuring work productivity uses a work productivity questionnaire. The results showed that there were 28 nurses who were tired (56.6%), the work productivity of nurses who were not suitable were 24 people (51.1%) and there were 4 people who were suitable (7.7%). There were 19 nurses (40.4%) who were not tired, 8 nurses (17.0%) who were not fit for work, and 11 nurses (23.4%) who were fit. There were 25 nurses (53.2%) who were dissatisfied, 25 nurses (53.2%) who were suitable for work productivity and none (0%) did not have suitable nurse productivity. There are 22 nurses who are satisfied (46.8%), the work productivity of nurses who are not suitable there are 7 people (14, 9%) and the work productivity of nurses who did not fit there were 15 people (31.9%). The relationship between work fatigue and job satisfaction with work productivity shows significant results (p <0.05). It is hoped that further research will be carried out on the factors that affect work productivity other than fatigue and satisfaction factors.